Exploring gender differences in language style: a style of male and female characters’ speech in English novels - Bayzakova, Maqpal Maxsud qizi (The Lingua Spectrum, 2026)
This article explores how gender affects language style by examining the speech of male and female characters in classic English novels. It focuses on significant language features including vocabulary, sentence structure, politeness strategy, hedging, and how to show emotions. These features are analyzed to understand how gender influences communication patterns in literature. Such analysis helps reveal underlying social expectations reflected in character dialogues across texts. As well as, the results show that female characters use more emotional and relational language, as well as more complicated sentence structures and ways that soften up their speech to keep their relationships strong. In contrast, male characters tend to use direct, succinct, and assertive modes of expression. These patterns are in line with what sociolinguistic researchers have said about how men and women talk to each other. Examples from chosen literary works demonstrate how dialogue mirrors broader societal norms. Moreover, the study emphasizes the significance of literature in depicting gendered communication and the necessity of linguistic analysis in understanding characters representation and cultural contexts.